High-entropy catalyst for CO hydrogenation catalytic synthesis of light olefins, and preparation method and application thereof
By solidly dissolving a variety of metal components, the high-entropy spinel catalyst is solved, and the problems of insufficient stability and reduced activity of traditional catalysts are achieved, and the catalytic effect of CO hydrogenation synthesis of olefins is achieved.
Patent Information
- Application Number
- CN202411752629.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional iron-based catalysts have problems of insufficient stability and reduced activity in the synthesis of olefins by CO hydrogenation, and a single metal additive cannot reflect the synergistic effect of high entropy multi-elements.
By solidly dissolving a variety of different metal components, a single-phase stable high-entropy spinel catalyst was formed. The catalyst was prepared by gel method to ensure that the crystal structure is maintained and the FeCo alloy is dissolved under hydrogen reduction conditions, thereby improving catalytic activity.
High stability and high selectivity of CO hydrogenation synthesis olefin catalysts are achieved, which improves CO conversion and light hydrocarbon selectivity and reduces by-product selectivity.
Smart Images

Figure CN119657163A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst materials, and in particular to a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, and a preparation method and application thereof. Background Art
[0002] As petroleum resources become increasingly scarce, there is an urgent need to find alternative resources. Therefore, people have begun to focus on finding clean, sustainable, and alternative green energy. Fischer-Tropsch synthesis uses synthesis gas (mainly CO and H2) to synthesize liquid fuels and high-value chemicals such as olefins, gasoline, and diesel under the action of catalysts. In addition, the direct production of low-carbon olefins from synthesis gas is a one-step reaction to generate the target product. Its process flow is simpler than the indirect method (CO2 and H2), and the economic evaluation is more cost-effective. In the past decade, the direct synthesis of low-carbon olefins from synthesis gas has begun to attract attention.
[0003] Traditional iron-based catalysts are widely used in CO hydrogenation catalysis due to their high activity, flexible reaction conditions, wide product adjustability, and low cost. However, traditional iron-based catalysts do not have a very stable crystal form and the surface active metal particles continue to agglomerate during the gradual catalytic reaction, which reduces the catalytic activity. High-entropy catalyst materials are made of five-element metal solid solutions. Compared with traditional catalysts, the synergistic effect of high-entropy multi-elements promotes the formation of active phases and maintains good stability during long-term catalysis. These advantages can achieve high activity and high selectivity for olefins. In addition, the results of relevant experimental studies and theoretical calculations at home and abroad have shown that in order to effectively improve product distribution and increase the selectivity of low-carbon olefins, electronic additives such as Mn, Zr, CO, Zn, etc. are generally added. They can adjust the chemical adsorption state of CO and H2 on the catalyst surface and promote the reduction of the catalyst to improve CO conversion and olefin selectivity. However, these single metal additives cannot reflect the synergistic effect of high entropy multi-elements and the maintenance of crystal structure during the reaction. Therefore, it is crucial to develop a high-entropy catalyst with high activity and high selectivity in the process of CO hydrogenation to olefins. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, and a preparation method and application thereof. The present invention forms a single-phase stable high entropy spinel catalyst by solid dissolving a plurality of different metal components, thereby improving the catalytic stability of the catalyst; at the same time, due to the stability of the high entropy structure, the catalyst maintains a complete crystal structure under the condition of hydrogen reduction, and dissolves FeCo alloy with smaller particles in the reduction position. This improves the catalytic activity of the catalyst, thereby obtaining a catalyst material for CO hydrogenation synthesis of olefins with high stability and selectivity.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] A method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, specifically comprising the following steps:
[0007] Step S1, dissolving iron salt, cobalt salt, zinc salt, manganese salt, chromium salt and sodium salt in deionized water, stirring evenly to obtain a mixed solution; adding citric acid to the mixed solution and continuing to stir for 40 to 80 minutes to obtain a uniform solution;
[0008] Step S2, placing the uniform solution obtained in step S1 in a water bath at 90° C. and stirring to form a uniform gel;
[0009] Step S3, placing the gel obtained in step S2 in an oven for drying at a drying temperature of 80-120° C.;
[0010] Step S4, placing the dried gel into a tubular furnace for calcination at a temperature of 800-1000° C. for 3 hours to obtain a finished high entropy spinel catalyst.
[0011] Furthermore, in step S1, the iron salt is one or more of ferric chloride trihydrate, ferric nitrate nonahydrate, and ferric acetate tetrahydrate; the cobalt salt is one or more of cobalt chloride dihydrate, cobalt nitrate trihydrate, and cobalt acetate monohydrate; the zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, and zinc acetate dihydrate; the manganese salt is one or more of manganese chloride tetrahydrate, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate; the chromium salt is one or more of chromium chloride trihydrate and chromium chloride octahydrate; and the sodium salt is sodium nitrate.
[0012] Furthermore, in step S1, the molar ratio of citric acid to total metal salt is 1:1. This molar ratio facilitates the subsequent formation of a uniform gel.
[0013] Furthermore, in step S1, the molar ratio of the iron salt, cobalt salt, zinc salt, manganese salt, chromium salt and sodium salt is (2-3): (2-3): 0.55: 1: 1: 1.
[0014] Furthermore, in step S1, the stirring time after adding citric acid is 60 minutes.
[0015] Furthermore, in step S3, the drying temperature is 100°C.
[0016] Furthermore, in step S4, the calcination temperature is 900°C.
[0017] A high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, wherein the high entropy catalyst is prepared by the above-mentioned preparation method.
[0018] An application of the high entropy catalyst for CO hydrogenation catalytic synthesis of light olefins, and the application of the high entropy catalyst in CO hydrogenation catalysis.
[0019] Furthermore, the application is specifically as follows: a high entropy metal catalyst is reduced with H2 and then loaded into a fixed fluidized bed, a mixed gas consisting of CO2 and H2 is introduced, and a hydrogenation reaction is carried out at a temperature of 300°C and a pressure of 1MPa, wherein the molar ratio of CO2 to H2 is 1:2.
[0020] The beneficial effects of the present invention are as follows: the present invention is reasonably designed and has the following advantages:
[0021] (1) The present invention uses a gel method to prepare a high entropy catalyst. The preparation method has simple process conditions and mild reaction conditions, which is conducive to large-scale production. At the same time, the synergistic catalysis of multiple metals in the high entropy catalyst can help form and stabilize the active phase. In addition, this method can make the catalyst dissolve the cobalt-iron alloy in situ during the hydrogen reduction process through the solid solution of multiple elements, which not only exposes more active sites, but also promotes the conversion of CO.
[0022] (2) The catalyst prepared by the present invention has the characteristics of high CO conversion rate, high selectivity of light hydrocarbons (ethylene, propylene, butene), low selectivity of by-products such as methane, etc. during the reaction process. At the same time, the high stability of the catalyst also improves the production efficiency of hydrocarbons and ensures the continuous progress of the reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 is the XRD pattern of the fresh catalyst in Examples 1 to 3 and Comparative Example 1;
[0025] Figure 2 is the XRD diagram of the reduced catalyst in Examples 1 to 3;
[0026] Figure 3 Graph showing the CO conversion rate of the catalysts in Examples 1 to 3 over time. DETAILED DESCRIPTION
[0027] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0028] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] A method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, specifically comprising the following steps:
[0031] Step S1, dissolving iron salt, cobalt salt, zinc salt, manganese salt, chromium salt and sodium salt in deionized water, stirring evenly to obtain a mixed solution; adding citric acid to the mixed solution and continuing to stir for 40 to 80 minutes to obtain a uniform solution;
[0032] Step S2, placing the uniform solution obtained in step S1 in a water bath at 90° C. and stirring to form a uniform gel;
[0033] Step S3, placing the gel obtained in step S2 in an oven for drying at a drying temperature of 80-120° C.;
[0034] Step S4, placing the dried gel into a tubular furnace for calcination at a temperature of 800-1000° C. for 3 hours to obtain a finished high entropy spinel catalyst.
[0035] In step S1, the iron salt is one or more of ferric chloride trihydrate, ferric nitrate nonahydrate, and ferric acetate tetrahydrate; the cobalt salt is one or more of cobalt chloride dihydrate, cobalt nitrate trihydrate, and cobalt acetate monohydrate; the zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, and zinc acetate dihydrate; the manganese salt is one or more of manganese chloride tetrahydrate, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate; the chromium salt is one or more of chromium chloride trihydrate and chromium chloride octahydrate; and the sodium salt is sodium nitrate.
[0036] In step S1, the molar ratio of citric acid to total metal salts is 1:1; the molar ratio of iron salt, cobalt salt, zinc salt, manganese salt, chromium salt and sodium salt is (2-3): (2-3): 0.55: 1: 1: 1; and the stirring time after adding citric acid is 60 minutes.
[0037] The drying temperature in step S3 is preferably 100°C.
[0038] The calcination temperature in step S4 is preferably 900°C.
[0039] A high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation is prepared by the above preparation method.
[0040] An application of the above-mentioned high entropy catalyst for CO hydrogenation catalytic synthesis of light olefins, the application of the high entropy catalyst in CO hydrogenation catalysis, specifically: the high entropy metal catalyst is loaded into a fixed fluidized bed after being reduced with H2, a mixed gas composed of CO2 and H2 is introduced, and a hydrogenation reaction is carried out at a temperature of 300°C and a pressure of 1MPa, wherein the molar ratio of CO2 to H2 is 1:2.
[0041] Example 1
[0042] A method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, specifically comprising the following steps:
[0043] Step S1, Fe(NO3)3·9H2O (1.616 g), Co(NO3)2·6H2O (1.164 g), Mn(NO3)2·6H2O (0.276 g), Zn(NO3)2·6H2O (0.594 g), Cr(NO3)3·9H2O (0.8 g), NaNO3 (0.17 g) were dissolved in 30 ml of deionized water (wherein the molar ratio of Fe:Co:Mn:Zn:Cr:Na was 2:2:0.55:1:1:1) and stirred for 30 min, then an appropriate amount of citric acid was added to the homogeneous solution (the molar ratio of citric acid to total metal nitrates was 1:1) and stirring was continued for 60 min to obtain a homogeneous solution;
[0044] Step S2, placing the uniform solution obtained in step S1 in a water bath at 90° C. and stirring to form a uniform gel;
[0045] Step S3, placing the gel obtained in step S2 in an oven for drying at a drying temperature of 100° C.;
[0046] Step S4: calcining the dried gel in a tubular furnace at 900°C for 3 hours to obtain a finished high entropy spinel catalyst (Fe2Co2Mn 0.55 ZnCrNa)3O4.
[0047] Experimental operation steps of the catalytic evaluation system: First, 0.4g of high entropy catalyst material and 1g of quartz sand are mixed, and then loaded into the middle position of the reaction tube of the Fischer-Tropsch device. In order to ensure that the quartz sand and catalyst block other gas pipes, a certain amount of quartz sand needs to be filled at both ends of the reaction tube. Then reinstall it into the high-pressure catalytic evaluation system for catalysis. The specific operation is as follows: The high entropy catalyst is first reduced by H2 (0.4MPa pressure, temperature 600℃, space velocity 1300ml / (g*h)), and after 2h, the reduced catalyst can be used for subsequent catalytic reactions. Then, when the reduction is completed, the catalyst is loaded into the reactor, and a CO / H2 mixed gas with a molar ratio of 1:2 is introduced. Light olefin products are prepared by hydrogenation at a temperature of 300℃, a pressure of 1MPa, and a space velocity of 1500ml / (g*h). The reaction time is 100h.
[0048] The average data within 100 hours was calculated and the CO conversion rate of the catalyst was 66.2%, the CH4 selectivity was 28.79%, and the C2 = -C4 = The selectivity is 39.8%, C5 + The selectivity is 23.47%.
[0049] Example 2
[0050] The difference from Example 1 is:
[0051] In this embodiment, step S1 is: Fe(NO3)3·9H2O (2.424g), Co(NO3)2·6H2O (1.164g), Mn(NO3)2·6H2O (0.276g), Zn(NO3)2·6H2O (0.594g), Cr(NO3)3·9H2O (0.8g), and NaNO3 (0.17g) are dissolved in 30ml of deionized water (wherein the molar ratio of Fe:Co:Mn:Zn:Cr:Na is 3:2:0.55:1:1:1) and stirred for 30min, then an appropriate amount of citric acid is added to the uniform solution (the molar ratio of citric acid to total metal nitrates is 1:1) and stirring is continued for 60min to obtain a uniform solution.
[0052] The operations of steps S2 to S4 are the same as those of Example 1.
[0053] The finished product obtained in this embodiment is a high entropy spinel catalyst (Fe3Co2Mn 0.55 ZnCrNa)3O4.
[0054] The catalytic reaction process was the same as in Example 1. The average data within 100 hours was calculated to obtain a CO conversion rate of 67.9%, a CH4 selectivity of 34.26%, and a C2 = -C4= The selectivity is 35.91%, C5 + The selectivity is 21.42%.
[0055] Example 3
[0056] The difference from Example 1 is:
[0057] In this embodiment, step S1 is: Fe(NO3)3·9H2O (1.616 g), Co(NO3)2·6H2O (1.746 g), Mn(NO3)2·6H2O (0.276 g), Zn(NO3)2·6H2O (0.594 g), Cr(NO3)3·9H2O (0.8 g), and NaNO3 (0.17 g) are dissolved in 30 ml of deionized water (wherein the molar ratio of Fe:Co:Mn:Zn:Cr:Na is 2:3:0.55:1:1:1) and stirred for 30 min, then an appropriate amount of citric acid is added to the uniform solution (the molar ratio of citric acid to total metal nitrates is 1:1) and stirring is continued for 60 min to obtain a uniform solution.
[0058] The operations of steps S2 to S4 are the same as those of Example 1.
[0059] The finished product obtained in this embodiment is a high entropy spinel catalyst (Fe2Co3Mn 0.55 ZnCrNa)3O4.
[0060] The catalytic reaction process was the same as in Example 1. The average data within 100 hours was calculated to obtain a CO conversion rate of 69.3%, a CH4 selectivity of 38.4%, and a C2 = -C4 = The selectivity is 33.38%, C5 + The selectivity is 19.37%.
[0061] Comparative Example 1
[0062] The difference from Example 1 is that step S1 of this comparative example is: Fe(NO3)3·9H2O (1.616 g), Co(NO3)2·6H2O (1.164 g), Mn(NO3)2·6H2O (0.276 g), Zn(NO3)2·6H2O (0.594 g), Cr(NO3)3·9H2O (0.8 g) are dissolved in 30 ml of deionized water (wherein the molar ratio of Fe:Co:Mn:Zn:Cr is 2:2:0.55:1:1) and stirred for 30 min, then an appropriate amount of citric acid is added to the uniform solution (the molar ratio of citric acid to total metal nitrates is 1:1) and stirring is continued for 60 min to obtain a uniform solution.
[0063] The operations of steps S2 to S4 are the same as those of Example 1.
[0064] The finished product obtained in this comparative example is a catalyst (Fe2Co2Mn 0.55 ZnCr)3O4
[0065] The catalytic reaction process was the same as in Example 1. The average data within 100 hours was calculated to obtain a CO conversion rate of 72.2%, a CH4 selectivity of 55.4%, and a C2 = -C4 = The selectivity is 15.9%, C5 + The selectivity is 16.4%.
[0066] The catalytic performance of the catalysts prepared in Examples 1 to 3 and Comparative Example 1 was tested. The test results are shown in Table 1.
[0067] Table 1 Catalytic performance of Examples 1 to 3 and Comparative Example 1
[0068]
[0069] Table 1 shows the average performance of the catalysts at different calcination temperatures within 100 hours. 0.55 The CO conversion rate of ZnCrNa)3O4 reached 66.2%, the selectivity of CH4 was 28.79%, and the selectivity of C2 = -C4 = The selectivity is 39.8%.
[0070] By comparing Examples 1 to 3, it can be seen that different ratios of Fe and Co in the high entropy catalyst have little effect on the conversion of CO, but have a significant effect on the conversion of C2 = -C4 = There is a clear difference in selectivity.
[0071] Figure 1 The XRD diagrams of the fresh catalysts in Examples 1 to 3 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the prepared catalysts all exhibited a Fe3O4 crystal structure, which ensured the successful preparation of a single-phase high entropy oxide. In addition, it can be observed that as the ratio between Fe and Co increases, the diffraction peaks of the crystals become sharper, which indicates larger crystal particles. For the reduction of Na in Comparative Example 1, (Fe2Co2Mn 0.55 ZnCr)3O4 and (Fe2Co2Mn 0.55 ZnCrNa)3O4 crystal form has no obvious change, but it can be seen from Table 1 that (Fe2Co2Mn 0.55 The selectivity of ZnCr)3O4 for CH4 increased to 55.4%, C2 = -C4 =The selectivity of CO hydrogenation decreased to 15.9%, which indicates that the addition of Na increased the basicity of the sample surface and affected the product distribution of CO hydrogenation.
[0072] Figure 2 is the XRD diagram of the catalyst after reduction in Examples 1 to 3, Figure 2 It can be seen that only (Fe2Co2Mn 0.55 ZnCrNa)3O4 maintains the Fe3O4 crystal structure while dissolving FeCo alloy in situ on the catalyst surface. (Fe3Co2Mn 0.55 ZnCrNa)3O4 and (Fe2Co3Mn 0.55 ZnCrNa)3O4 crystals collapsed obviously, and there were larger particles of FeCo alloy on the surface. In summary, it can be concluded that (Fe2Co2Mn 0.55 ZnCrNa)3O4 has the best catalytic activity and high light olefin selectivity due to its good crystal integrity and smaller active centers.
[0073] Figure 3 Graph showing the change in CO conversion rate of the catalysts in Examples 1 to 3 over time. Figure 3 It can be seen that after 75 hours of long-life experiment, the prepared catalyst has a stable CO conversion rate over time, which also provides a guarantee for subsequent practical applications.
[0074] In summary, the present invention is reasonably designed and has the following advantages:
[0075] (1) The present invention uses a gel method to prepare a high entropy catalyst. The preparation method has simple process conditions and mild reaction conditions, which is conducive to large-scale production. At the same time, the synergistic catalysis of multiple metals in the high entropy catalyst can help form and stabilize the active phase. In addition, this method can make the catalyst dissolve the cobalt-iron alloy in situ during the hydrogen reduction process through the solid solution of multiple elements, which not only exposes more active sites, but also promotes the conversion of CO.
[0076] (2) The catalyst prepared by the present invention has the characteristics of high CO conversion rate, high selectivity of light hydrocarbons (ethylene, propylene, butene), low selectivity of by-products such as methane, etc. during the reaction process. At the same time, the high stability of the catalyst also improves the production efficiency of hydrocarbons and ensures the continuous progress of the reaction.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, characterized in that: The specific steps include: Step S1, dissolving iron salt, cobalt salt, zinc salt, manganese salt, chromium salt and sodium salt in deionized water, stirring evenly to obtain a mixed solution; adding citric acid to the mixed solution and continuing to stir for 40 to 80 minutes to obtain a uniform solution; Step S2, placing the uniform solution obtained in step S1 in a water bath at 90° C. and stirring to form a uniform gel; Step S3, placing the gel obtained in step S2 in an oven for drying at a drying temperature of 80-120° C.; Step S4, placing the dried gel into a tubular furnace for calcination at a temperature of 800-1000° C. for 3 hours to obtain a finished high entropy spinel catalyst.
2. The method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation according to claim 1, characterized in that: In the step S1, the iron salt is one or more of ferric chloride trihydrate, ferric nitrate nonahydrate, and ferric acetate tetrahydrate; the cobalt salt is one or more of cobalt chloride dihydrate, cobalt nitrate trihydrate, and cobalt acetate monohydrate; the zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, and zinc acetate dihydrate; the manganese salt is one or more of manganese chloride tetrahydrate, manganese nitrate tetrahydrate, and manganese acetate tetrahydrate; the chromium salt is one or more of chromium chloride trihydrate and chromium chloride octahydrate; and the sodium salt is sodium nitrate.
3. The method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation according to claim 1, characterized in that: In step S1, the molar ratio of citric acid to total metal salt is 1:
1.
4. The method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation according to claim 1, characterized in that: In the step S1, the molar ratio of the iron salt, cobalt salt, zinc salt, manganese salt, chromium salt and sodium salt is (2-3): (2-3): 0.55: 1: 1:
1.
5. The method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation according to claim 1, characterized in that: In the step S1, the stirring time after adding citric acid is 60 minutes.
6. The method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation according to claim 1, characterized in that: In step S3, the drying temperature is 100°C.
7. The method for preparing a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation according to claim 1, characterized in that: In the step S4, the calcination temperature is 900°C.
8. A high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation, characterized in that: The high entropy catalyst is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation as claimed in claim 8, characterized in that: Application of the high entropy catalyst in CO hydrogenation catalysis.
10. The use of a high entropy catalyst for catalytic synthesis of light olefins by CO hydrogenation according to claim 9, characterized in that: The application is specifically as follows: a high entropy metal catalyst is reduced with H2 and then loaded into a fixed fluidized bed, a mixed gas consisting of CO2 and H2 is introduced, and a hydrogenation reaction is carried out at a temperature of 300°C and a pressure of 1MPa, wherein the molar ratio of CO2 to H2 is 1:2.
Citation Information
Patent Citations
Supported non-noble metal catalyst as well as preparation and application thereof
CN108114723A
Molten iron catalyst for preparing low-carbon olefin from synthesis gas as well as preparation method and application of molten iron catalyst
CN114011423A
Preparation method of high-entropy oxide sodium ion battery positive electrode material
CN115207341A
Perovskite type high-entropy oxide and preparation method and application thereof
CN115837275A
High-entropy oxide doped and coated co-modified positive electrode material, preparation method and application
CN117223124A